O impacto do tratamento ortodôntico na autoestima e na qualidade de vida de pacientes adultos com necessidade de reabilitação - Nascimento, Vanessa de Couto (2015)
The aim of this study was to evaluate if orthodontic treatment in adults requiring oral rehabilitation is effective for increasing patients´ self-esteem and quality of life. The sample consisted of 102 adult patients (77 women and 25 men) aged between 18 and 66 years requiring oral rehabilitation and orthodontic treatment simultaneously. The Rosemberg´s Self-esteem Scale (RSE) and a questionnaire about quality of life based on the Oral Health Impact Profile (OHIP-14) were used to determine self-esteem and quality of life scores retrospectively. Questionnaires were carried out in two stages, T1 (start of treatment) and T2 (after the initial phase alignment and leveling-6 months). In order to compare the score changes between T1 and T2, data obtained from RSE were evaluated with paired t test and the questionnaire of quality of life data was assessed by applying descriptive statistics. The results showed a statistically significant increase in self-esteem (p <0.001) and a great improvement on patients´ quality of life. Orthodontic treatment generates a significant increase in self-esteem and quality of life, providing psychological benefits for adult patients in need of oral rehabilitation.